Unchaining Collective Intelligence for Science, Research, and Technology Development by Blockchain-Boosted Community Participation - Ducrée, Jens; Etzrodt, Martin; Bartling, Sönke; Walshe, Ray; Harrington, Tomás; Wittek, Neslihan; Posth, Sebastian; Wittek, Kevin; Ionita, Andrei; Prinz, Wolfgang; Kogias, Dimitrios; Paixão, Tiago; et al. (Frontiers in Blockchain, 2021)
Since its launch just over a decade ago by the cryptocurrency Bitcoin, the distributed ledger technology (DLT) blockchain has followed a breathtaking trajectory into manifold application spaces. This paper analyses how key factors underpinning the success of this ground-breaking “internet of value” technology, such as staking of collateral (“skin in the game”), competitive crowdsourcing, crowdfunding and prediction markets, can be applied to substantially innovate the legacy organization of science, research and technology development (RTD). Here, we elaborate a highly integrative, community-based strategy where a token-based crypto-economy supports finding best possible consensus, trust and truth through adding unconventional elements known from reputation systems, betting, secondary markets and social networking. These tokens support the holder’s formalized reputation, and are used in liquid-democracy style governance and arbitration within projects or community-driven initiatives. This participatory research model serves as a solid basis for comprehensively leveraging collective intelligence by effectively incentivizing contributions from the crowd, such as intellectual property (IP), work, validation, assessment, infrastructure, education, assessment, governance, publication and promotion of projects. On the analogy of its current blockbusters like peer-to-peer structured decentralized finance (“DeFi”), blockchain technology can seminally enhance the efficiency of science and RTD initiatives, even permitting to fully stage operations as a chiefless Decentralised Autonomous Organization (DAOs).